Aplicación de TBL en el aula (Journal of Parents and Teachers, 2021)
The Thinking Based Learning (TBL) methodology is based on creating thinking strategies to create skills and abilities in students so that they are able to learn to think at the same time as they learn the curricular content.
Keywords: methodology; teaching to think; strategies; skills; metacognition; TBL